2020
DOI: 10.3103/s0095452720060031
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Study of COVID-19 Corona Virus Excludes Its Origin from Recombination or Characterized Biological Sources and Suggests a Role for HERVS in Its Wide Range Symptoms

Abstract: The COVID-19 corona virus has become a world pandemic which started in December 2019 in Wuhan, China with no confirmed biological source. Various countries reported the genomic sequence of different isolates obtained from infected patients. This allowed us to obtain a number of 38 isolates of full genomic sequences. Alignment of nucleotide (nt) sequence was carried out using Clustal Omega multiple alignment service at the EBI website. Alignment of nt sequence and phylogenetic relationship revealed that the COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 78 publications
(109 reference statements)
1
10
0
Order By: Relevance
“…4A), as well as SARS-CoV-2-infected human epithelial lung cells and macrophages (Fig. 4B and C), which has occasionally been reported in the last few months for cell lines and patients [28][29][30][31]. Among the analysed REs, LINE1 are strongly represented in all results (Fig.…”
Section: Transcriptome Analysis Of Retroelements In Sars-cov-2-infect...supporting
confidence: 63%
See 1 more Smart Citation
“…4A), as well as SARS-CoV-2-infected human epithelial lung cells and macrophages (Fig. 4B and C), which has occasionally been reported in the last few months for cell lines and patients [28][29][30][31]. Among the analysed REs, LINE1 are strongly represented in all results (Fig.…”
Section: Transcriptome Analysis Of Retroelements In Sars-cov-2-infect...supporting
confidence: 63%
“…While the inhibition of SARS-CoV-2 replication has already been achieved [5][6][7][8][9][10], the factors driving the late phase of the disease are poorly understood [11,12]. However, it has been reported that autoimmunity [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and deregulation of human retroelements (RE) might contribute to the outcome of COVID-19 patients [28][29][30][31]. about 25 % £ 6 aa, but only a few at 4 aa [55]).…”
Section: Introductionmentioning
confidence: 99%
“…Being predictive of a severe prognosis, ENV expression could play a role in immune overactivation and contribute to acute and chronic COVID-19 complications ( 135 ). In this context, HERVs could act as endogenous modulators of SARS-CoV-2/host interaction, helping to explain the extreme inter-individual variability in COVID-19 manifestations ( 136 ). Along this line, potential interplays of Herpesviruses and HERVs with SARS-CoV-2 might also be conceivably supposed to impact on MS pathogenesis and affect disease course.…”
Section: Sars-cov-2 and Ms-associated Viruses: Partners In Crime?mentioning
confidence: 99%
“…HERVs may play a role in SARS-CoV-2 infection and COVID-19 symptoms (El-Shehawi et al 2020 ). HERVs or their viral products might promote the infection and penetrance of the virus to human cells, or HERVs may produce proteins that regulate the translation start for the ribosome changing the pattern of COVID-19 ORFs in different human hosts; thus the severity and course of the COVID-19 infection would differ.…”
Section: Hervs In Human Diseasesmentioning
confidence: 99%
“…Although vaccination against SARS-CoV-2 helps protect from COVID-19, some people are hesitant to the vaccinations for a number of reasons, including a rumor that concerns a cross-activity of anti-SARS-CoV-2 spike protein syncytin-1 in the placenta. Also, some recent reports show the differentially expressed HERVs in COVID-19 patients, suggesting that HERVs may be involved in COVID-19 epidemiology (El-Shehawi et al 2020 ; Kitsou et al 2021 ; Marston et al 2021 ). On the other hand, it has been reported that CRP level increases in serum from COVID-19 patients and positively correlates with disease severity (Chen et al 2020 ; Luo et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%